Qua Vadis Pendidikan Agama Islam Berbasis Multikulturalime di Indonesia - Rosady, Imron (Medan Resource Center, 2022)
This study examines topics relating to Islamic religious education using research in education that is multicultural in nature. The study of quo vadis Islamic Religious Education based on multiculturalism in Indonesia forms the basis of this research, which is based on a review of the relevant literature. In order to respond to some of the research questions in this paper, this study employs a qualitative descriptive analytic methodology. First, how is Indonesia's understanding of Islamic religious education? Second, what does the term